Quality of life and functional disability in patients with interstitial lung disease related to Systemic Sclerosis - Lumetti, Federica; Barone, Lissette; Alfieri, Cristina; Silva, Mario; Serra, Valter; Delsante, Giovanni; Sverzellati, Nicola; Ariani, Alarico (Acta Biomedica Atenei Parmensis, 2015)
Background: Systemic Sclerosis (SSc) is a connective disease impairing respiratory function. SSc worsens patients’ Health Assessment Questionnaire (HAQ-DI), Short Form 36 Physical and Mental Component Summary (SF36-PCS and SF36-MCS). The aim of this work is to verify whether there is correlation between quality of life and lung interstitiopathy in SSc patients. Methods: SF36 and HAQ-DI were given to each patient (48 in all). Lung involvement was evaluated with Baseline Dyspnea Index (BDI), spirometry and pulmonary fibrosis radiological assessment (PFRA). Correlations between SF36, HAQ-DI and lung involvement severity were investigated with Spearman’s rank test. A p-value<0.05 was considered statistically significant. Results: SF36-PCS and SF36-MCS correlate with BDI (respectively rho=0.553 p=0.0001; rho=0.357 p=0.0150). The best correlating SF36 subsets are Physical Role (rho =0.566 p<0.0001) and Bodily Pain (rho=0.444 p=0.0020). BDI correlates with HAQ-DI (rho=-0.655 p<0.0001). No statistically significant correlation was found between SF36, HAQ-DI and spirometrical values nor PFRA. Conclusions: The SSc patients enrolled have an impaired quality of life as widely demonstrated in literature. Quality of life reduction and functional ability decrease are only related to respiratory subjective impairment (assessed by BDI). Actually no correlation with objective lung damage (assessed by spirometry and PFRA) was detected.